STRATEGI MANAJEMEN HUMAS DALAM MENYAMPAIKAN PROGRAM UNGGULAN MADRASAH - Nurul, Nurul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2018)
Madrasah as an educational unit that provides the basics to follow education in the next level it is necessary to realize its excellent urgent owned madrasah.Salah an effort to madrasah with the implementation of Madrasah-based management, one of them public relations management. Public Relations is the development and maintenance of efficient cooperation to deliver a two-way information channel between the Madrasah and the community outside Madrasah. Public Relations management in conveying the advantages that exist in the madrasah aims specifically to answer the problems: (1) Management of public relations in improving the quality of madrasah, (2) Supporting factors and inhibitors faced in public relations management. (1) PR management in improving the quality of madrasah (2) Supporting factors of public relations management: a) Human resources (HR) teachers who have motivation and high performance and the average young age, b) Madrasahs in under the Foundation c) High achievement of madrasah, d) High public interest in bringing their children to Madrasah e) stakeholders supporting madrasah activities such as cooperation with Erlangga textbook publishers, LKS Sansekerta Jakarta, Bank Syariah Mualamat, Bank Syariah Mandiri, Dannis Surabaya home in procurement of Madrasah uniforms as well as Ummi Foundation Surabaya in Qiraati Al Qur'an, f) strategic madrasah location. The inhibiting factor in public relations management is the absence of sub-section or head of affairs (kaur) which specifically handles public relations so that public relations programs have not run optimally and the participation level of parents in the public relations program is not fully maximized.